A Review on Headaches Due to COVID-19 Infection - Togha, Mansoureh; Hashemi, Seyedeh Melika; Yamani, Nooshin; Martami, Fahimeh; Salami, Zhale (Frontiers in Neurology, 2022)
Since December 2019, the time when the severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) was spotted, numerous review studies have been published on COVID-19 and its neuro invasion. A growing number of evidence have reported headache as a common neurological manifestation of COVID-19. Although several hypotheses have been proposed regarding the association between headache and the coronavirus, no solid evidence has been presented for the mechanism and features of headache in COVID-19. Headache also is a common complaint with omicron variant of the virus. Covid-19 vaccination also is a cause of new onset headache or aggravation of previous headache in migraine or tension headache sufferers. In this review study, the types of headaches reported in previous studies and their possible pathogenic mechanisms are outlined. To accomplish this objective, various types of headache are classified and their patterns are discussed according to ICHD-3 diagnostic criteria, including, headache attributed to systemic viral infection, viral meningitis or encephalitis, non-infectious inflammatory intracranial disease, hypoxia and/or hypercapnia, cranial or cervical vascular disorder, increased cerebrospinal fluid (CSF) pressure, refractive error, external-compression headache, and cough headache. Then, their pathogeneses are categorized into three main categories including, direct trigeminal involvement, vascular invasion, and inflammatory mediators. Furthermore, persistent headache after recovery and the predictors of intensity is further investigated. Post vaccination headache is also discussed in this review.